Lecture 1. Intermolecular Forces Liquids & Solids, Part I - Donald R. Blake (University of California Irvine (UCI), 2013)
(en)UCI Chem 1B is the second quarter of General Chemistry and covers the following topics: properties of gases, liquids, solids; changes of state; properties of solutions; stoichiometry; thermochemistry; and thermodynamics. Index of Topics: 0:48:33 First to Measure Gases: Gay Lussac 0:50:24 Genealogy (Academic Heritage) 0:51:38 Stratospheric Chemistry 0:57:54 CFC 1:01:00 Cicerone and Stolarski (Catalytic Cycle) 1:05:26 What are the effects fo reduced stratospheric ozone? 1:06:45 DNA Mutation 1:07:49 Ozone Graph 1:09:40 Weather balloon Photos 1:10:14 Ozone Over McMurdo Station, Antartica 1:12:25 Polar Stratospheric Clouds 1:13:45 Concentration vs Time Graph 1:14:01 South Pole Photos